SYNTHESIS OF AMYL VANILLIL ETHER AS WARMING AGENT FROM VANILLIN - Budimarwanti, C.; Theresih, Karim (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2015)
Synthesis of amyl vanillyl ether from vanillin was carried out by two different methods, two-steps reaction method and one-step reaction method. In two-steps reaction method beginning with the first stage reduction of vanillin with NaBH4 to obtain vanillyl alcohol. Then, dehydration vanillyl alcohol and amyl alcohol with concentrated sulfuric acid. Synthesized compound were identification by TLC, IR spectroscopy and GCMS. In one step reaction method the vanillyl alcohol as a result of reduction of vanillin with NaBH4 are not isolated in advance, immediately reacted with amyl alcohol to form amyl vanillyl ether compound with concentrated HCl dehydrator. The results of two-steps reaction method showed that the reduction reaction of vanillin with NaBH4 produced vanillyl alcohol. Vanillyl alcohol compound that produced is white powder and yield 41.28%. Vanillyl amyl ether compound could not synthesis by dehydration from vanillyll alcohol from reduction of vanillin and amyl alcohol. Ether compound from dehydration of vanillyl alcohol from reduction of vanillin and amyl alcohol is diamyl ethers. Method one reaction step successfully synthesized amyl vanilil ether compound. Amyl vanilil ether compound that produced is liquid, colorless and yield 86.42%. Keywords: amyl vanillil ether, vanillin, vanillil alcohol, amyl alcohol